Utlization Cat Swarm Optimization Algorithm for Selected Harmonic Elemination in Current Source Inverter - Hamed Hosseinnia; Murteza Farsadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The voltage source inverter (VSI) and Current source inverter (CSI) are two types of traditional power inverter topologies.In this paper selective harmonic elimination (SHE) Algorithm was impelemented to CSI and results has been investigated. Cat swarm (CSO) optimization is a new meta-heuristic algorithm which has been used in order to tuning switching parameters in optimized value.Objective fuction is reduction of total harmonic distortion(THD) in inverters output currents.All of simulation has been carried out in Matlab/Software.